China's industrial policies and the global business revolution : the case of the domestic appliance industry - Liu, Ling, 1969- (Routledge studies on the Chinese economy, 2005)
As China has blended market reforms with comprehensive industrial policies, most research has focused on the national government's strategies for economic growth. However, one of the unique characteristics of industrial policy in China is that it involves government intervention at all levels, from the political elite all the way down to village leaders.This book focuses on the domestic appliance industry, and China's three major business groups in this area - Haier, Hisense and Aucma. The Haier Group, in particular, is one of the most successful and competitive enterprises in China.